ANALISA PENGARUH BRAND EQUITY TERHADAP KINERJA KEUANGAN INDUSTRY RETAIL DI SURABAYA - Eranio Randy (Business Accounting Review, 2015)
The purpose of this study was to determine the affect on the financial performance of brand equity and use customer satisfaction as an intervening variable. This study was conducted using questionnaires, the research sample 35 retail companies located in Surabaya,. This study aimed to determine the extent of influence the Brand Equity Performance Fianancial retail companies. The survey results revealed that, Brand Equity significant positive affect on Financial Performance direct and significant negative indirect relationship with Customer Satisfaction as an intervening variable.